2022
DOI: 10.3390/agronomy12051096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microgreens Biofortification with Selenium on Their Quantitative and Qualitative Parameters

Abstract: The study monitored the effect of differentiated mineral nutrition of microgreens species by solution of sodium selenate (2 mg Se/L) on the content of Se, chlorophylls, and other minerals. Chlorophylls were measured spectrophotometrically, Se by electrothermal atomic absorption method (ETAAS) with Zeeman-effect background and elements' concentration was performed by a dual Inductively coupled plasma atomic emission spectroscopy (ICP-OES) iCAP7600 instrument. The content of selenium in fresh weight moved on ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…The greatest biomass was obtained for green pea enriched with Se (3.1 ± 0.5 g DW per cup), and the lowest was alfalfa enriched with Se (0.9 ± 0.2 g DW per cup), which have a similar growing time. This work is in agreement with previous studies where similar concentrations of Se (13–32 μM) applied to different types of microgreens did not reduce the plant biomass. ,, In addition, note that no toxicity effects were found on the different plant species throughout the growth period, such as chlorosis, dry leaves, growth retardation, or wilting.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The greatest biomass was obtained for green pea enriched with Se (3.1 ± 0.5 g DW per cup), and the lowest was alfalfa enriched with Se (0.9 ± 0.2 g DW per cup), which have a similar growing time. This work is in agreement with previous studies where similar concentrations of Se (13–32 μM) applied to different types of microgreens did not reduce the plant biomass. ,, In addition, note that no toxicity effects were found on the different plant species throughout the growth period, such as chlorosis, dry leaves, growth retardation, or wilting.…”
Section: Resultssupporting
confidence: 93%
“…30 In our study, the concentration of Ca in green pea and red radish was not significantly affected by Se biofortification; however, a significant decrease in Ca of 37% and magnesium (Mg) of 26% was observed in alfalfa biofortified with Se, compared with the control. Mezeyováet al 28 and Pannico et al 3 obtained similar results in some microgreens, where Ca was negatively affected 31 observed that in Zea mays tissues, the accumulation of Ca, Mg, Zn, Cu, and Fe is strongly related to the Se concentration and the inorganic form in which it was introduced into the nutrient solution. Ca plays a crucial role in osmoregulation and in maintaining the cation− anion balance, while Mg is essential for plant pigment synthesis and the activation of many enzymatic systems of photosynthesis and respiration.…”
Section: Influence Of Se Biofortification On Mineralmentioning
confidence: 66%
See 1 more Smart Citation
“…The enhancement of food with biochemicals can be achieved through biofortification methods in microgreen plants. 21 Although the benefits of soilless culture in general and in microgreen plant production have been investigated by various crop science disciplines including crop improvement and crop production, in order to further advance its practice, techniques of soilless cultivation and comprehensive compilation and investigation of plant production, factors affecting plants, biofortification, artificial light mechanisms in plant growth, pathway regulation, or nutrient enhancement, and nanoparticles in plant growth and stress tolerance under water based culture and substrate based culture conditions are needed 22 (Figure 1). Details of these aspects are reviewed in this work: i. to explore microgreen plant production in soilless culture, ii.…”
Section: Advantages and Disadvantages Of Microgreensmentioning
confidence: 99%
“…The concentration ranges of 0.15–150 mg/L zinc fortified shoot biomass and zinc content in cabbage or broccoli genotype in an unheated glasshouse through peat growing media . Supplying 2 mg/L selenium improved calcium content in green basil and cress, potassium and zinc content in arugula and green basil, zinc content in cress and radish, and barium content in green basil and cress in a climatic chamber with a phytotron system through rockwool growing media …”
Section: Biofortification In Microgreen Plantsmentioning
confidence: 99%